Defusing currency crises Empirical evidence from emerging market-economies - Aguinaldo, Joseph Michael J. (ProQuest Dissertations & Theses Global, 1999)
"The behavior of policy and state variables is compared between episodes of defused and full-blown currency crises for 22 emerging-market economies. Currency crises are identified by an index of exchange market pressure derived from a monetary model of exchange rate determination. Using graphical tools, non-parametric statistical tests and logit estimation, this paper finds no evidence of expansionary fiscal or monetary policies prior to full-blown currency crises. It also finds that in an environment of declining output, rising unemployment and high inflation, currency intervention is ineffective in defusing a currency crisis and that, in a crisis situation, contractionary monetary policy is effective in stabilizing the exchange rate."--Abstract.